Thyroid hormone and vitamin D regulate VGF expression and promoter activity - Lewis, Jo E.; Brameld, John M.; Hill, P.J.; Wilson, Dana; Barrett, Perry; Ebling, Francis J.P.; Jethwa, Preeti H. (Bioscientifica, 2015)
The Siberian hamster (Phodopus sungorus) survives winter by decreasing food intake and catabolizing abdominal fat reserves, resulting in a sustained, profound loss of body weight. Hypothalamic tanycytes are pivotal for this process. In these cells, short-winter photoperiods upregulate deiodinase 3, an enzyme that regulates thyroid hormone availability, and downregulate genes encoding components of retinoic acid (RA) uptake and signaling. The aim of the current studies was to identify mechanisms by which seasonal changes in thyroid hormone and RA signaling from tanycytes might ultimately regulate appetite and energy expenditure. proVGF is one of the most abundant peptides in the mammalian brain, and studies have suggested a role for VGF-derived peptides in the photoperiodic regulation of body weight in the Siberian hamster. In silico studies identified possible thyroid and vitamin D response elements in the VGF promoter. Using the human neuroblastoma SH-SY5Y cell line, we demonstrate that RA increases endogenous VG expression (P!0.05) and VGF promoter activity (P!0.0001). Similarly, treatment with 1,25-ihydroxyvitamin D3 increased endogenous VGF mRNA expression (P!0.05) and VGF promoter activity (P!0.0001),whereas triiodothyronine (T3) decreased both (P!0.01 and P!0.0001). Finally, intrahypothalamic administration of T3 blocked the short day-induced increase in VGF expression in the dorsomedial posterior arcuate nucleus of Siberian hamsters. Thus, we conclude that VGF expression is a likely target of photoperiod-induced changes in tanycyte-derived signals and is potentially a regulator of seasonal changes in appetite and energy expenditure.